PENGARUH PENDAPATAN DAERAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI JAWA TIMUR - Devi, Larasati Eka; Harmono, Harmono; Sisharini, Nanik; Respati, Harianto (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2024)
Economic growth is a process of continuous change in the economic condition of a country towards a better situation over a certain period. An economy is said to experience a change in its development if the level of economic activity is higher than previously achieved.Â This study is used to analyze the effect of regional income on gross regional domestic product in East Java. The independent variables in this study are local revenue, revenue sharing funds, general allocation funds and special allocation funds, while the dependent variable in this study is gross regional domestic product.Â This type of research is explanatory research using descriptive analysis, multiple linear regression analysis, classical assumption test and hypothesis testing.Â The results showed that Regional Original Revenue (PAD) had a significant positive effect on Gross Regional Domestic Product (GRDP), Revenue Sharing Fund (DBH) had a significant positive effect on Gross Regional Domestic Product (GRDP), General Allocation Fund (DAU) had a significant positive effect on Gross Regional Domestic Product (GRDP) while Special Allocation Fund (DAK) had no significant positive effect on Gross Regional Domestic Product (GRDP).